2024
DOI: 10.1680/jcoma.21.00063
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional performance of biopolymers and biocement in stabilisation of road bases

Abstract: To achieve the sustainability goals, Australia must dramatically reduce use of cement for stabilisation of soil used in road bases. Bio-based binders for soil stabilization are potential alternatives. Biocementation through Microbially Induced Calcite Precipitation (MICP) is well researched. Some research on biopolymeric stabilization is also available. This paper explores the synergistic effect of combined biopolymer and biocement for the stabilization of sandy soil and road bases. The soil has been stabilise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Findings would give further insights into improving resource use efficiency in MICP treatments. Furthermore, a reduction in the use of Portland cement for the stabilisation of soil, for applications such as road bases [30], will contribute to achieving the UN Sustainable Development Goals.…”
Section: Co(nhmentioning
confidence: 99%
“…Findings would give further insights into improving resource use efficiency in MICP treatments. Furthermore, a reduction in the use of Portland cement for the stabilisation of soil, for applications such as road bases [30], will contribute to achieving the UN Sustainable Development Goals.…”
Section: Co(nhmentioning
confidence: 99%
“…For instance, Kumar et al [26] observed a significant increase in the strength under the unconfined strength compression (USC) test when the soil contained substantial clay contents. Ramachandran et al [27] noted that incorporating xanthan gum into soil improves roadbed stability. Nikseresht et al [28] demonstrated that the addition of sugar cane molasses and vinasse enhances calcium carbonate production.…”
Section: Introductionmentioning
confidence: 99%